Empirical juridical review of traffic accident by Underages (study of accident cases in the east banjarmasin region) - Adna Giovanni Dasdjar; Muhammad Mahendra Abdi; Deni Nofrizal (LEGAL BRIEF, 2023)
Traffic accident is an incident on the road that is unexpected and unintentional involving vehicles with or without other road users which results in loss and/or loss of property. Underage are children under 17 years of age. Most of the traffic violators who are caught in raids are generally dominated by minors and do not have a driver's license (SIM). This study aims to discuss the empirical juridical review of traffic accidents committed by minors (case study of accidents in the East Banjarmasin region). The method used in this research is empirical juridical method.The re-sults of the study show that the sanctions for traffic accidents committed by underage given by the Banjarmasin Police, especially the East Banjarmasin area, are to provide punishment or sanctions and legal processes that take place in cases of violation of the law. In the provisions for imposing action sanctions, based on not being 14 (fourteen) years old as stipulated in Article 69 paragraph (2) of Law No. 11 of 2012 that children who are not yet fourteen (14) years old can only be subject to action sanctions, while the provisions for criminal sanctions given to children based on the age above 12 (twelve) years and up to 18 (eighteen) years. Some of the efforts made by the Banjarmasin Police included making banners containing appeals. Collaborating with Jasa Raharja and the De-partment of Transportation in socializing the traffic safety awareness program. Visiting schools to provide information about the proper use of vehicles and the need to comply with traffic rules on the roads